Entrepreneurial Orientation and the Performance of the Agro-allied Enterprises in Akwa Ibom State, Nigeria - Nsikak-Abasi A. Etim; Edet J. Udoh; Enobong E. King (Journal of Social Commerce, 2022)
It is widely recognized that Small and Medium Enterprises (SMEs) are the major drivers of sustainable economic growth, sources of income generation and panacea for poverty reduction in developing countries. Unfortunately, they are faced with numerous challenges that threaten their existence and survival. This precarity of small entrepreneurial organizations in entrepreneurial ecosystem has prompted widespread attention by scholars and researchers. Hence, it is critical to take into consideration examining the performance of the enterprises. This study analyzed the effect of entrepreneurial orientation dimensions, personal and institutional characteristics on the performance of small and medium agro allied enterprises. Through the multistage sampling procedure, a total of 198 SMEs were selected for the study and data were collected with the aid of questionnaire. Data were analyzed using multiple regression analysis. Results revealed that among the entrepreneurial orientation dimensions, only risking taking and innovativeness significantly and positively affected the performance of SMEs agro allied enterprises. Furthermore, findings showed that except for size of business which was negatively related to the growth of SMEs, educational level of entrepreneurs, managerial and business experience positively and significantly impacted on the performance of SMEs. Policies to encourage SMEs invest in risky investments and create new product and services should be pursued.